Double Hexagon: A Human-Centred Design Framework for Innovation - Motamer, Vajiheh Aida (My University, 2021)
Healthcare systems need to adjust services and methods to accommodate the needs, desires, and capabilities of people. Experience-Based Co-Design (EBCD) is the state of the art in participatory service design within the UK National Health Service (NHS), that draws upon design tools and ways of thinking in order to bring healthcare staff and patients together to improve the quality of care. The Co-design process that is integral to the EBCD approach is powerful but also challenging, as it requires active collaboration among multidisciplinary teams, including organizational stakeholders (e.g., investors, managers, advocates, etc.), end-users (e.g., staff, patients, carers, etc.), designers/researchers, and developers. Over the last decade, given the evaluation of the EBCD approach, there has been a gap between theory and practice resulting in limited outcomes in healthcare service improvements. Systematic reviews suggest this low success results from the lack of a systematic elaboration of Co-Design methods, limited tools and insufficient guidance on the ideation process, the tendency to develop a solution without enough divergent thinking, and a poor structure of participation. In order to improve health care services and address the gaps mentioned, we propose a methodology called Double Hexagon, that includes principles of Co-Design, Human-Centred Design, and Design Thinking. This framework is a Human-Centred Design framework that seeks to assist designers and non-designers in moving from designing “product” categories to designing for “people” by providing a concrete and step-by-step realization for “Designing for People”.
Keywords: Human-Centred Design;User Experience;Design Thinking;Co-Design; Experienced-Based Co-Design;Innovation;Healthcare Service Interventions